Using Moodle to Foster Learners’ Autonomy In literature classes (The case study of Master one English students at Ammar Thelidji University-Laghouat - Neggaz ,Hayat; BenAissa ,Aicha; BOUMEDIENE, Houda (Faculty of Letters and Foreign Languages Department of English, 2019)
This work is part of broader project that investigates the impact of the use of Moodle as a pedagogical platform in enhancing learners' autonomy as well as in improving their learning skill. One major problem within Algerian university s is the lack of independency which can be related to students' ignorance of the significance of being autonomous. In order to highlight the attitudes and behavior of learners toward the use of information and communication technology in higher education. At the same time we wanted to know wether teachers are confident in using this platform in their classes. Hense, after giving the questionnaire to master one English students and interviewing five teachers of literature working in the field of . Results have shown that those ICT(Information Communication Technology)in Ammar Thelidji university. These questions have to do with their experiences of applying this system and wether can help learners to be autonomous. The work has a descriptive nature ;the results obtained in this study revealed that the majority of investigated learners have a very positive attitude towards the use of Moodle pedagogical platform ,provided that better technical and techno-pedagogical support and training on the computer-based teaching tool will be adapted to the learners’ needs. Besides, the results are in favor of promoting the updating of teaching methods, use of very adequate teaching resources, rapid dissemination of teaching evaluations and facilitating the organization of students ‘working time .By doing this research, we hope that learners will be familiar with the concept of autonomy and more aware of its importance in fostering their learning process. We hope also that teachers will recognize the significant role of Moodle in helping learners be autonomous inside and outside the classroom